#### Answer

$\frac{x+7}{x-5}$

#### Work Step by Step

$\frac{x^2+8x+7}{x^2-4x-5}$
$=\frac{(x+7)(x+1)}{(x-5)(x+1)}$
$=\frac{x+7}{x-5}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$\frac{x+7}{x-5}$

$\frac{x^2+8x+7}{x^2-4x-5}$
$=\frac{(x+7)(x+1)}{(x-5)(x+1)}$
$=\frac{x+7}{x-5}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.